The impact of oil price volatility on stock market returns: evidence from ASEAN countries - Seah, Jiang Ghee (2019)
This research examines the impact of oil price volatility on stock market returns in ASEAN countries (Indonesia, Malaysia, Philippines, Singapore, Thailand and Vietnam) by using daily data for the period of 3rd January 2005 to 31st May 2018. According to the economic theories, oil price causes range of effects on real economic activities. The performance of stock market also being affected by oil price violations. In order to measure oil price volatility, E-GARCH model is used in this study. Brent oil price and West Texas Intermediate (WTI) oil price are collected for this research. Subsequently, the effects of oil price volatility on stock market returns of each country is examined by applying OLS regression method. In addition, the relationship between oil price volatility and stock market returns during 2008 global financial crisis is investigated. The impacts of oil price volatility during pre-crisis period and post-crisis period for each country are also analysed. The results indicate that oil price volatility is generally not significant on stock market returns in most of the ASEAN countries, except for the oil price volatility of Brent crude oil on stock market returns of Malaysia and Thailand.